Priorities for collaborative research using very preterm birth cohorts - Zeitlin, J (2020)
Objectives To develop research priorities on the consequences of very preterm (VPT) birth for the RECAP Preterm platform which brings together data from 23 European VPT birth cohorts. Design and setting This study used a two-round modified Delphi consensus process. Round 1 was based on 28 research themes related to childhood outcomes (<12 years) derived from consultations with cohort researchers. An external panel of multidisciplinary stakeholders then ranked their top 10 themes and provided comments. In round 2, panel members provided feedback on rankings and on new themes suggested in round 1. Results Of 71 individuals contacted, 64 (90%) participated as panel members comprising obstetricians, neonatologists, nurses, general and specialist paediatricians, psychologists, physiotherapists, parents, adults born preterm, policy makers and epidemiologists from 17 countries. All 28 initial themes were ranked in the top 10 by at least six panel members. Highest ranking themes were: education (73% of panel members' top 10 choices); care and outcomes of extremely preterm births, including ethical decisions (63%); growth and nutrition (60%); emotional well-being and social inclusion (55%); parental stress (55%) and impact of social circumstances on outcomes (52%). Highest ranking themes were robust across panel members classified by background. 15 new themes had at least 6 top 10 endorsements in round 2. Conclusions This study elicited a broad range of research priorities on the consequences of VPT birth, with good consensus on highest ranks between stakeholder groups. Several highly ranked themes focused on the socioemotional needs of children and parents, which have been less studied.